Aplikasi Pembelajaran Rangkaian Listrik Sederhana Berbasis Android - Palit, Henry Novianus; Setiawan, Alexander (Jurnal Infra, 2016)
Physics is one of the science subjects which learns about natural phenomena in our surroundings. One of the topics learnt in physics is Electric Circuit. Many people nowadays lack the understanding of the theories, calculation formulae, and practices of the electric circuit. Even though the electric circuit is indispensable and one of the physics topics that is used in everydayâs life. People are often not interested in learning theories and formulae from the book, while the electric circuits practices require components and supporting substances. This leads to a new matter because sometimes there are substances that are too hard to find and get.This manuscript discusses the development of an Android-based application for learning simple electric circuits. Android is chosen because it is one of the smartphones operating systems that is aggresively growing. This application employs a drag and drop method, which consists of dragging the desired object and dropping it at a particular position. The application was developed using Java programming language, Eclipse, and MySQL as its database.Based on the system testing that has been done, the developed application allows a user to login to the system, register him/herself, display simple electric circuit materials, display simulation that will be useful for the user in designing a simple electric circuit with its specified components and the calculation, try quizzes to test his/her knowledge, display users scores, and update materials and quizzes. This application needs internet connection to register, login, display images, and update data.